(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Mozambique from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.5 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will slightly decline over the out of sample period but still remain high. Therefore, there is need to scale up of HIV testing, ART coverage and prevention services among this age group. In addition, there is need to address top drivers of HIV spread among this age group.